2016
DOI: 10.1159/000444799
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2a Study of Benralizumab for Patients with Eosinophilic Asthma in South Korea and Japan

Abstract: Background: Airway eosinophils are considered to play an important role in the pathogenesis of asthma. Interleukin-5 is believed to be a key cytokine for the development, proliferation and activation of eosinophils. Benralizumab is an anti-interleukin-5 receptor α monoclonal antibody that depletes blood and airway eosinophils. We conducted a phase 2a study in South Korea and Japan to evaluate the effect of benralizumab in an East Asian population. The primary objective was to evaluate the effect of benralizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 25 publications
(31 reference statements)
0
51
0
1
Order By: Relevance
“…Targeting eosinophils by blocking IL-5 or its receptor is a novel approach for asthma treatment. Benralizumab, an anti-IL-5 receptor antibody, has been demonstrated to significantly reduce the number of asthma exacerbations and to increase the forced expiratory volume in 1s, FEV 1 , in an Asian population [9]. Recent observations demonstrate a role for the IL-25/IL-25 receptor axis in asthma, thus also identifying this as a novel therapeutic target [10].…”
Section: Toward New Therapies For Asthmamentioning
confidence: 99%
“…Targeting eosinophils by blocking IL-5 or its receptor is a novel approach for asthma treatment. Benralizumab, an anti-IL-5 receptor antibody, has been demonstrated to significantly reduce the number of asthma exacerbations and to increase the forced expiratory volume in 1s, FEV 1 , in an Asian population [9]. Recent observations demonstrate a role for the IL-25/IL-25 receptor axis in asthma, thus also identifying this as a novel therapeutic target [10].…”
Section: Toward New Therapies For Asthmamentioning
confidence: 99%
“…The degree of heterogeneity measured by the I 2 statistic was not signi cant, so an analysis using a fixed-effect model was conducted. Because only one trial investigated the effects of benralizumab 20 and 100 mg on injection site reactions and pyrexia or in uenza-like illness 10 , metaanalyses for these outcomes could not be performed. Only non-inferiority tests and comparisons between low-and high-dose groups were conducted.…”
Section: Adverse Events Injection Site Reactions and Pyrexia Or In mentioning
confidence: 99%
“…Several randomized controlled trials RCTs have examined the effects of benralizumab, an anti-IL-5 receptor monoclonal antibody, on uncontrolled eosinophilic asthma [10][11][12] , with the results showing that a relatively high dose of benralizumab 100 mg signi cantly reduces exacerbation rates and improves asthma symptoms and quality of life 10 12 . A relatively low dose 20 mg of benralizumab also reduces exacerbation rates in patients with uncontrolled eosinophilic asthma and has a lower incidence of adverse effects 10 , but the non-inferiority of low-versus high-dose benralizumab remains untested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized controlled trials RCTs have examined the effects of benralizumab BRZ , an anti-IL-5 receptor monoclonal antibody, on uncontrolled asthma [7][8][9] . The results showed that a relatively low dose of benralizumab 30 mg / body significantly reduced exacerbation rates and improved both asthma symptoms and the quality of life in patients with uncontrolled asthma 10 11 .…”
Section: Introductionmentioning
confidence: 99%